Prevention of cardiovascular events with antiplatelet treatment: does time of intake matter for aspirin and ADP receptor blockers? - Sibbing, Dirk; Gross, Lisa; Aradi, Dániel (Thrombosis and Haemostasis, 2016)
Long-term evidence supports a clustering of cardiovascular events in the early morning. Several studies have shown that platelet hyper-reactivity to various stimuli is also present at this period of the day. However, the idea of treatment strategies reflecting the circadian variation in platelet reactivity has been largely neglected so far, and this is true despite the huge number of patients being treated with these drugs. Some pharmacodynamic data suggest that early-morning platelet hyper-reactivity may be overcome by shifting aspirin intake to the bedtime. However, there is lack of evidence whether shifting the time of intake or splitting the daily dose of P2Y12-inhibitors with a regular QD dosing (clopidogrel or prasugrel) to the evening would be effective to overcome platelet hyper-reactivity or to suppress the excess of cardiovascular events observed during morning hours. Further research is warranted to clarify whether such a simple and costless effort like dose shifting or splitting may be beneficial to prevent cardiovascular events.
Keywords: ADP receptors; antiplatelet agents; clinical trials; antiplatelet drugs; platelet pharmacology